(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The aftermath of an earthquake manifests great devastation due to unpredicted seismic motion striking extensive damage to innumerable buildings of varying degree, i.e. either full or partial. This damage to structures in turn causes irreparable loss of life with a large number of casualties. Strengthening of structures proves to be a better option catering to the economic considerations and immediate shelter problems rather than replacement of buildings. Moreover it has been often seen that retrofitting of buildings is generally more economical as compared to demolition and reconstruction. Therefore, seismic retrofitting or strengthening of building structures is one of the most important aspects for mitigation seismic hazards especially in earthquake prone areas. Seismic strengthening or retrofitting is generally carried out in two ways either global retrofit methods or local retrofit methods. In this study, the seismic performance of reinforced concrete (RC) buildings with shear walls is studied. The effect of shear walls on lateral capacity of the building has been examined. For this purpose RC building with and without shear walls has been analyzed. The performance of the building is evaluated using parameters such as time period, lateral displacement, base shear and storey drift. It is observed from the present study that the shear wall system improves not only the lateral stiffness and strength capacity but also the displacement capacity of the structure. The seismic performance of the frame also depends upon location of shear walls and its symmetry. Hence, addition of shear walls in existing buildings is an effective tool for seismic strengthening like the other methods of retrofitting. In this project attempt is made to understand the Seismic performance of building with shear wall and without shear wall. The main objective of this project is to find out which will have better seismic performance either building with shear wall or building without shear wall. In present study RCC building models having G+9 stories with shear wall and without shear walls considered for analysis. The analysis of model is done using equivalent static method in ETABS software. Finally the results of seismic behavior of buildings are compared with respect to time period, base shear, storey shear, member forces, overturning moment, displacement, stiffness and drifts.